PENGARUH RELAKSASI OTOT PROGRESIF TERHADAP KUALITAS TIDUR IBU HAMIL PRIMIGRAVIDA - Tirta Mulyana; Sri Utami; Arneliwati Arneliwati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2019)
During pregnant the mother will experience psychological changes and physical changes, one of pshysical changes experienced is a sleep disorder, so that pregnant women will be difficult to meet and needs and the quality of sleep becomes worse sleep quality is very important for pregnant women, if the quality of the sleep is distrubed will affect to the mother and fetus. This study aims to determine the effect of progressive muscle relaxation on the sleep quality of primigravidian pregnant women. The research design used was quasi experimental with a non equivalent control group. The sample of this study was 34 respondents with the sampling technique using purposive sample and divided into 2 groups namely the experimental and control groups. The measuring instrument used was the PSQI (Pittsburgh Sleep Quality Index) questionnaire. The results of the statistical test performed were obtained by the median sleep quality score after progressive muscle relaxation in the experimental group is 5,00 and the control group is 7,00. While the Mann Whitney test result obtained p value (0,000) <α (0.05), so it can be concluded that there is a significant effect of progressive muscle relaxation on the sleep quality of primigravidian pregnant women. Keywords: primigravida pregnant women, progressive muscle relaxation, sleep quality